2007
DOI: 10.1002/ibd.20049
|View full text |Cite
|
Sign up to set email alerts
|

Does colonoscopy cause increased ulcerative colitis symptoms?

Abstract: In our study, 1 in 8 subjects had UC relapse by SCCAI immediately postcolonoscopy, and 1 in 10 subjects required an increase in their 5-ASA medications. Clinicians should be cognizant of this effect of colonoscopy in patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 35 publications
1
43
1
Order By: Relevance
“…14,15 The high prevalence of prior performed colonoscopy in patients with CP/CPPS could be explained by colonoscopy itself, which may stimulate the pelvic floor resulting in pelvic floor muscle spasms.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The high prevalence of prior performed colonoscopy in patients with CP/CPPS could be explained by colonoscopy itself, which may stimulate the pelvic floor resulting in pelvic floor muscle spasms.…”
Section: Discussionmentioning
confidence: 99%
“…Some publications have found that IBD patients reported low satisfaction from the bowel preparation compared to other patients [89] . Moreover, some ulcerative colitis patients have reported flare symptoms after colonoscopy [90] . The reasons for these negative experiences are unknown, but bowel preparation could be a contributing factor.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…There is evidence to suggest colonoscopy2 and bowel preparation3 may have caused the exacerbation of ulcerative colitis leading to toxic megacolon.…”
Section: Descriptionmentioning
confidence: 99%